Using feelings and emotions in the EFL classroom to improve writing skills through story writing workshops - Pinto Pérez, Lina Paola (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper aims at analyzing the role that feelings and emotions play when they are utilized inside the EFL classroom with eighth grade students. They were encouraged to talk about their feelings and emotions through the development of ten workshops based on writing short stories from their own life experiences. The results showed that feelings and emotions are a part of students that cannot be ignored because they are a factor in the learning process. Self-directed learning and a positive classroom environment are also key factors that should be considered in addition to the students’ emotional side when learning English as a foreign language.